2009
DOI: 10.1016/j.saa.2008.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The spectroscopic detection of drugs of abuse in fingerprints after development with powders and recovery with adhesive lifters

Abstract: The application of powders to fingerprints has long been established as an effective and reliable method for developing latent fingerprints. Fingerprints developed in situ at a crime scene routinely undergo lifting with specialist tapes and are then stored in evidence bags to allow secure transit and also to preserve the chain of evidence. In a previous study we have shown that exogenous material within a fingerprint can be detected using Raman spectroscopy following development with powders and lifting with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 11 publications
0
34
0
2
Order By: Relevance
“…Additional information in a forensic context, such as the use by or recent exposure of an individual to illicit drugs, could provide enhanced evidence between a fingermark and a suspect. The successful detection of cocaine and other drug compounds in latent fingermarks is known using a number of different analytical approaches, and is particularly well-described for prints artificially doped with the compound of interest [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional information in a forensic context, such as the use by or recent exposure of an individual to illicit drugs, could provide enhanced evidence between a fingermark and a suspect. The successful detection of cocaine and other drug compounds in latent fingermarks is known using a number of different analytical approaches, and is particularly well-described for prints artificially doped with the compound of interest [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The immunodetection of cocaine on banknotes is limited to the application of strip-based immunoassays originally developed for qualitative detection of the drug in urine [24,25]. The detection of cocaine extracted from doped fingerprints is similarly focused on MS-based approaches, such as desorption electrospray ionization (DESI)-MS [15] and SALDI-TOF-MS [16] or Raman spectroscopy [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work we had already obtained reference spectra from all the seized samples [1,2]. This also enabled us to remove from the study any samples with fluorescence problems that could not be diminished by photobleaching.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies we have demonstrated the ability to use Raman spectroscopy to characterise drugs of abuse present in latent fingerprints following development with powders and recovery with adhesive lifters [1,2]. Other work has shown that samples of pure drugs can be detected on clothing using Raman spectroscopy [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation